Type A aortic dissection: Why there is still a role for echocardiography when every second counts. (December 2020) - Luke, Peter; Booth, Karen; Kindawi, Ali; Eggett, Christopher
Aortic dissection is often regarded as a catastrophic aortic syndrome with high rates of mortality. The sensitivity and specificity of transthoracic echocardiography when diagnosing acute type A aortic dissection has been reported as high as 97% and 100%, respectively, in patients with optimal imaging quality when compared to computed tomography. In this article, we discuss the benefit of transthoracic echocardiography in a patient with type A aortic dissection extending from ascending aorta to iliac arteries.